A semiotic analysis of Arthur’s King journey in Guy Ritchie’s King Arthur: Legend of the Sword (2017) film - Muhammad Nur Fauzi; Alamsyah Tawakkal (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
This research examined the symbolic meanings of Arthur's journey to becoming king in the film King Arthur: Legend of the Sword (2017) by Guy Ritchie. The background of this research highlighted the importance of symbols in culture and media, as well as the role of semiotic approaches in interpreting the implied meanings within the film. The purpose of this research is to analyze the signs that reflect Arthur's transformation into the rightful king. This research employed a qualitative descriptive method with a semiotic approach as proposed by Roland Barthes through the system of signification: denotation, connotation, and myth. Data were collected through the observation of visual, audio, and utterance elements in the film. The research findings indicated that there are 15 signs in Arthur’s journey towards self-discovery as king that are reflected through these signs, which consist of objects, animals, mental experiences, people, and myths that accompanied his emotional and spiritual transformation until he became king. The 11 main signs include The Sword in the Stone or Excalibur, Water, Street, Nightmare, Prostitutes, Eagle, The Darklands, Vision, Lady of the Lake, The Mage, and The Round Table. Additionally, there are 4 supporting signs: Snake, Giant Bat, Giant Rats, and Giant Wolf. These signs represent the concepts that shaped the entirety of Arthur's journey to becoming king. Arthur, who grew up on the streets, strives to free himself from the shadows of his dark past and the pressure of a destiny he has yet to understand.